Fundamentals of polymer engineering - Kumar, Anil; Gupta, Rakesh K. (CRC Press, Taylor & Francis Group, 2019)
"This textbook for a first course on polymers assumes some familiarity with thermodynamics and transport phenomena.It covers physical and chemical aspects and the concept of property being determined by structure. It discusses polymer synthesis, associated kinetics and molecular weights and uses this information for reactor design. It covers emulsion polymerization, polymer characterization and thermodynamics, and behavior of polymers as melts, solutions and solids. It examines crystallization, diffusion of and through polymers, polymer processing, and introduces new information on polyolefin technology, biobased plastics, and post-consumer plastic recycling. Chapters updated throughout"...